Heterophylly in Cordaites-like foliage from western Gondwana - Hünicken, Mario (2013)
Cordaitalean plants are an important component of upper Palaeozoic Gondwanan plant fossil assemblages. New fossil axes from western Argentina exhibit the first examples of heterophylly in Gondwanan cordaitaleans. Cordaites bifolius sp. nov.was probably a large tree, with its largest branches reaching 17 cmin diameter and leaves reaching at least 55 cm in length. Heterophylly is expressed by the co-attachment of spathulate and needle-like leaves in the twigs. The branches that preserve leaf scars are similar to species of Cordaicladus. Associated stout fertile organs are similar to Cordaitanthus and bear seeds of Cordaicarpus-type.